A populational-based birth cohort study in a low-income urban area in Rio de Janeiro, Brazil: implementation and description of the characteristics of the study - Renata Saraiva Pedro; Marilia Sá Carvalho; Vania Reis Girianelli; Luana Santana Damasceno; Izabel Leal; Denise Cotrim da Cunha; Liège Maria Abreu de Carvalho; Tania Ayllón; Mayumi Duarte Wakimoto; Jennifer Braathen Salgueiro; Laith Yakob; Nildimar Alves Honório; et al. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: A comprehensive cohort study including an entomological surveillance component can contribute to our knowledge of clinical aspects and transmission patterns of arbovirosis. This article describes the implementation of a populational-based birth cohort study that included an entomological surveillance component, and its associated challenges in a low-income community of Rio de Janeiro, Brazil. The participants were recruited in two periods: from 2012 to 2014, and from 2015 to 2017. The children had scheduled pediatric consultations and in case of fever. Epidemiological, clinical data and biological samples were collected at pediatric visits. Active febrile surveillance was performed by telephone calls, social networking, message apps, and household visits. A total of 387 newborns and 332 new children were included during the first and second recruitment periods, respectively. By July 2017, there were 451 children on follow-up. During the study, 2,759 pediatric visits were performed: 1,783 asymptomatic and 976 febrile/rash consultations. The number of febrile or rash consultations increased 3.5-fold after the use of media tools for surveillance. No temporal pattern, seasonality or peak of febrile cases was observed during the study period. A total of 10,105 adult mosquitoes (including 3,523 Aedes spp. and 6,582 Culex quinquefasciatus) and 46,047 Aedes eggs were collected from households, schools, and key sites. Although challenging, this structured sentinel populational-based birth cohort is relevant to the knowledge of risks and awareness of emerging pathogens.